2013
DOI: 10.1002/art.38012
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Methotrexate‐First Strategy in Patients With Early, Poor‐Prognosis Rheumatoid Arthritis: Results From a Two‐Year Randomized, Double‐Blind Trial

Abstract: Objective Methotrexate (MTX) taken as monotherapy is recommended as the initial disease-modifying antirheumatic drug for rheumatoid arthritis (RA). The purpose of this study was to examine outcomes of a blinded trial of initial MTX monotherapy with the option to step-up to combination therapy as compared to immediate combination therapy in patients with early, poor-prognosis RA. Methods In the Treatment of Early Rheumatoid Arthritis (TEAR) trial, 755 participants with early, poor-prognosis RA were randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
10

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 36 publications
4
51
0
10
Order By: Relevance
“…O'Dell et al 60 presented very similar results to those provided in Moreland et al 58 It was reported that no statistically significant difference was observed between the percentage of patients in each treatment modality (immediate combination treatment vs. step-up treatment) who discontinued treatment by week 24 (p = 0.84). Nor was any statistically significant difference observed between the percentage of patients in each treatment modality (immediate combination treatment vs. patients who stepped up treatment at week 24 vs. patients who remained on MTX monotherapy at week 24) who discontinued treatment between weeks 24 and 102 (p = 0.86).…”
Section: Assessment Of Cost-effectivenesssupporting
confidence: 59%
See 4 more Smart Citations
“…O'Dell et al 60 presented very similar results to those provided in Moreland et al 58 It was reported that no statistically significant difference was observed between the percentage of patients in each treatment modality (immediate combination treatment vs. step-up treatment) who discontinued treatment by week 24 (p = 0.84). Nor was any statistically significant difference observed between the percentage of patients in each treatment modality (immediate combination treatment vs. patients who stepped up treatment at week 24 vs. patients who remained on MTX monotherapy at week 24) who discontinued treatment between weeks 24 and 102 (p = 0.86).…”
Section: Assessment Of Cost-effectivenesssupporting
confidence: 59%
“…Eleven trials [26][27][28][29][30][31][32][33][34][35][36][38][39][40][41][42][43][44][45][46][47][48][49]51,[54][55][56][57][58][59][60]62,[64][65][66][67] examined an early RA population (defined as disease duration of < 3 years; see Chapter 4, Inclusion and exclusion criteria) [i.e. BehandelStrategieën in Reumatoïde Artritis (BeSt), 26- 55 the TreaTing to Twin Targets (T-4) study, 56,57 the Treatment of Early Aggressive Rheumatoid arthritis (TEAR) trial [58][59][60] and the early rheumatoid arthritis treated with tocilizumab, methotrexate or their combination (U-Act-Early) trial 62 ], three trials 9,50,52,53 examined an established RA population [i.e. British Rheumatoid Outcome Study Group (BROSG) trial, 9 Fransen et al 50 and the Optimisation of Adalimumab study 52,53 ] and two trials 61,63 examined populations that i...…”
Section: Assessment Of Clinical Effectivenessmentioning
confidence: 99%
See 3 more Smart Citations